SANTA CLAUS SOLIDARITY FOR PALESTINE: A SEMIOTIC ANALYSIS OF THE MOHAMMAD TOROKMAN’S PHOTOJOURNALISM - Novan Jemmi Andrea (The Indonesian Journal of Communication Studies, 2020)
Mohammad Torokman is a photojournalist with the Reuters News Agency. Torokman's photojournalism is chosen as "Picture of the Month: December" Reuters in 2017. The photo shows a picture of protesters dressed as Santa Claus throwing stones at the Israeli army when Palestinian protest against unilateral claims by the United States to make Jerusalem the capital of Israel. Torokman's photojournalism not only just evidence of a mere protest, but it has a message and a deeper meaning. This research discusses the denotation and connotation meaning of Torokman’s photojournalism using the semiotics theory of Roland Barthes. This research is descriptive qualitative. This research concludes that Torokman's photojournalism has two meanings: solidarity and resistance. In the first level of analysis, Torokman's photojournalism shows the protestor's opposition to the Israeli army. On the second level of analysis shows the meaning of solidarity, which is shown through joint struggle without regard to religion and belief to maintain its territory in Jerusalem.